Nonlinear output response of acousto-optic modulated distributed bragg reflector (DBR) fiber laser - Lai, M.H.; Islam, M.R.; Lim, K.S.; Fang, S.D.; Yang, H.Z.; Qiao, X.G.; Ahmad, Harith (National Institute of Optoelectronics, 2016)
This article presents a study on the output response of a distributed Bragg reflector (DBR) to acousto-optic wave. In the fabrication, the DBR is constructed with a 12 cm long EDF and two FBGs that share the same center wavelength. The behavior of the DBR under the influence of acousto-optic wave can be well explained based on the model of a single sinusoidal-modulated FBG. A nonlinear response has been observed for DBR output amplitude which is similar to the reflectivity variation at the center wavelength of an FBG impinged by acousto-optic wave. The potential for using DBR as a vibration sensor has been investigated in the frequency range of 120 kHz-190 kHz.